Implementación de un módulo para la automatización de procesos industriales para el laboratorio de la Universidad Técnica de Cotopaxi Extensión La Maná. - Chimbo Cevallos, Jhericoo Yholaus (2023)
This study focuses on the creation and development of a didactic module for the automation of industrial processes in the laboratory of the Technical University of Cotopaxi, La Mana extension. Currently, automation is essential to improve efficiency and growth in various industries, the use of advanced technologies and industrial systemsis key to maximi ze productivity, reduce costs and minimize human errors. The objective of this research is to provide electromechanical engineering students with a useful and effective learning environment, where they can practice the automation of industr ia l processes. For this, various components and technologies will be used, including sensors, Arduino, PLC, pilot lights and signal transmitters. The implementation of this module offers significant benefits for teaching, improving experience, accuracy and efficiency in processes, reducing human errors and saving time and resources. As a result of the research problem that lies in the lack of a module with sensors and control and force systems in the electromechanical laboratory, which makes practical learning in industrial automation difficult, in addition, the lack of adequate infrastructure and the high cost of Industrial components present additional challenges.This research project seeks to improve the teaching of industrial automation through the implementation of a didactic module at the La Mana Extension Technical University of Cotopaxi, offering practical learning opportunities and favoring the development of essential skills for future professionals in the field of electromechanics.